ECONOMIC RELATIONS OF ASEAN (INDONESIA) + CHINA AFTER AIIB - M. Dudi Hari Saputra (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2017)
This paper purpose is to predict Economic Relations of ASEAN(Indonesia) + China After AIIB (the Asian InfrastructureInvestment Bank), answering economic crisis questioned that hitthe United States and the European Union in 2009 and is still inthe recovery process until now, and has made many of Asiancountries particularly East Asia such as China began adiversification of market and investment destination and increaseeconomic cooperation to the other regions (ASEAN), particularlyIndonesia. Therefore, at first, this paper tries to analyze Chinaeconomic relations with Indonesia. Second, the effective rate ofChina trade and investment in Indonesia. Third, prediction ofIndonesia and China economic situation after AIIB cooperation.Indonesia relate governance with national policy, which will becorrelated with the level of supranational/regionalintergovernmental (regionalism and integration) which aims,among others; financial sector to stimulate research anddevelopment, increase the spread of technology, reducingmanagerial differences in running the business and implementinga system to change for the better.